Отцы и дети: [романы] / Иван Тургенев - Тургенев Иван Сергеевич (Мировая классика, 2017)
Экземпляры: (20201124) / Инвентарный номер: 4879 / Цена: / Сис.шифр: 84(2=411.2)5 / Авт.знак: Т 87 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)5